2012
DOI: 10.18388/abp.2012_2107
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia-modified albumin (IMA) is increased in patients with chronic hepatitis C infection and related to markers of oxidative stress and inflammation.

Abstract: Inflammation and oxidative stress have been reported in patients with chronic hepatitis C (CHC) infection, but their influence on ischemia-modified albumin (IMA) levels and diabetes prevalence remains unknown. Sixty-three CHC patients, 28 with diabetes, and 40 healthy controls were enrolled in the study. Circulating levels of oxidative stress markers [Nε-(carboxymethyl)lysine- advanced glycation end products (CML-AGEs) and advanced oxidation protein products-(AOPPs)], pro-inflammatory cytokines (interleukin-6,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…In addition, they found that IMA levels were higher in patients with hemorrhage when compared to patients without hemorrhage. A similar relationship was revealed by Zuwała-Jagiełło et al between IMA and inflammation in chronic hepatitis C patients with diabetes [48].…”
Section: Study (Number Of Patients) [Reference Number] Usefulsupporting
confidence: 85%
“…In addition, they found that IMA levels were higher in patients with hemorrhage when compared to patients without hemorrhage. A similar relationship was revealed by Zuwała-Jagiełło et al between IMA and inflammation in chronic hepatitis C patients with diabetes [48].…”
Section: Study (Number Of Patients) [Reference Number] Usefulsupporting
confidence: 85%
“…One of the objectives of the current study was to investigate the association between IM and bilirubin. It has been demonstrated that oxidative stress serves a crucial role in the pathogenesis of various infections, including the hepatitis virus ( 37 ), respiratory viruses ( 38 ), human immunodeficiency virus ( 39 ), influenza virus ( 40 ), Staphylococcus aureus ( 41 ), Helicobacter pylori ( 42 ) and mycoplasma ( 43 ). It is hypothesized that an infection due to EBV may also cause oxidative stress, leading to the marked depletion of antioxidants, such as bilirubin.…”
Section: Discussionmentioning
confidence: 99%
“…These authors found that oxidative stress occurred in CHC patients and serum levels of AOPPs were significantly elevated compared to the control group. Zuwała‐Jagiełło et al studied AOPPs in 63 patients with CHC infection. The plasma levels of AOPPs in the patients with CHC infection were significantly higher than those in healthy subjects.…”
Section: Data Sourcesmentioning
confidence: 99%